Gastrointestinal Problems in Overweight and Obese Individuals with Prader-Willi Syndrome (P21-033-19) - Alyousif, Zainab (Curr Dev Nutr, 2019)
OBJECTIVES: Individuals affected by Prader-Willi Syndrome (PWS) exhibit altered body composition, depressed metabolic rate and hyperphagia, leading to morbid obesity if not managed by life-long energy restriction. The extent of gastrointestinal problems in this population has been less studied. The aim of this cross-sectional study was to assess the prevalence of gastrointestinal (GI) symptoms, GI-related hospitalizations and surgeries, use of GI-related medications, and their associations to weight status in a cohort of individuals affected by PWS. METHODS: Data on height, weight, age, GI symptoms, GI-related hospitalizations and surgeries, and use of GI medications in an international cohort of individuals affected by PWS (n = 764) was collected from patients and caregivers through a PWS research website. Associations among age, weight, and GI outcomes were evaluated. RESULTS: As expected, overweight and obesity increased with age (P < 0.0001). Constipation (P < 0.05), diarrhea (P < 0.01), and stomach pain (P < 0.05) increased with BMI, whereas acid reflux decreased with BMI (P < 0.01). Diarrhea and stomach pain were higher in overweight and obese individuals compared to those of normal weight (P < 0.05). Acid reflux was lower in overweight and obese patients (P < 0.01). GI-related hospitalizations were not related to weight status. GI surgeries significantly decreased with patients’ weight (P < 0.05), higher in normal weight individuals compared to those overweight or obese (P < 0.05). The reported use of GI medications increased with body weight (P < 0.0001) and thus, was higher in overweight and obese individuals (P < 0.01). CONCLUSIONS: The cross-sectional data suggest that weight status of individuals affected by PWS may impact GI symptoms, GI-related surgeries, and the use of GI-related medications, but not GI-related hospitalizations. FUNDING SOURCES: Kingdom of Saudi Arabia Doctoral Scholarship.